PELAKSANAAN PERJANJIAN HAK PAKAI TOKO / KIOS ANTARA PEDAGANG DAN DINAS PERDAGANGAN KOTA PADANG DI PASAR RAYA PADANG - Diko Fazrian; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The market is an important place for humans to carry out various economictransactions, the market is a place that provides clothing, food, and shelter needs to meetthe primary needs of humans.The existence of Pasar Raya Padang is managed by thegovernment, namely the Trade Office of the City of Padang. In the implementation of theagreement to use the store / kiosk at the Padang highway market loaded in the bookholder of the right to use the shop / kiosk owned by the trader, in the book there areseveral articles, precisely in Article 3 reads "the second party promises not to change theform of a shop or kiosk and other facilities available without written consent from the firstparty ". The facts that occur in the field of traders change the form of shops / kioskswithout the knowledge of the first party, namely the Trade Dinaas of Padang City.The problem that the author makes the basis of this research is how theimplementation of the right to use store agreements between traders and the Padang CityTrade Service at the Padang highway market and how the process of problem solving inthe agreement to use the store between traders and the Padang City Trade Service. Thepurpose of this research is to find out the implementation of the agreement between themerchant and the Padang City Trade Service in Pasar Raya Padang and to find out theprocedures for resolving the problems that occur in the agreement to use the storebetween the trader and the Padang City Trade Service.This type of research can be classified into the type of empirical or sociologicalresearch, because in this study the author immediately conducts research on the locationor place under study in order to provide a complete and clear picture of the problemunder study. This research was conducted at the Padang highway market and PadangTrade Office, the data sources used were: primary data and secondary data, datacollection techniques in this study by observation, interviews and literature review.The results of this study are first.The implementation of the right to use the store or kiosk agreement in the Padangmarket is not in accordance with the rights to use the store or kiosk made by traders withthe Padang City Trade Service, in fact traders still violate the provisions of the rightsholders' book using Article 3, namely traders are prohibited from changing the form of aviolating trader given sanctions in the form of written warnings or fines ranging from Rp.500,000-Rp. 2,000,000 (five hundred thousand rupiahs-two million rupiahs), secondly,settlement of problems related to the agreement to use the store or kiosk at the Padanghighway market through several stages of the first stage of providing written warnings totraders who violate the next stage of conducting the negotiation process if they do not getan agreement, the Padang City Trade Service takes decisions in accordance with therights holder's book using a shop or kiosk namely unilaterally canceling the agreement.